A Critical Note on Treatment of a Severe Diltiazem Intoxication: High‐Dose Calcium and Glucagon Infusions. Issue 5 (22nd June 2017) - Van Veggel, Mathilde; Van der Veen, Gijs; Jansen, Tim; Westerman, Elsbeth
Abstract: The morbidity and mortality of a severe calcium channel blocker intoxication is high due to serious toxic cardiac effects. Its treatment is supported by low‐quality evidence from the heterogeneous literature. We describe a case of a severe diltiazem intoxication and critically appraise the efficacy and role of high‐dose calcium and glucagon infusions. A 53‐year‐old woman was admitted to the emergency department with a cardiogenic shock with complete AV block, not responding to atropine, isoprenaline and an external pacemaker. Later on, it became clear that she had a severe diltiazem intoxication which was successfully treated with isotone fluids, inotropes, vasopressors and continuous infusion of high‐dose calcium and glucagon. The patient developed, however, an acute, necrotizing pancreatitis, probably related to iatrogenic high calcium levels. This case demonstrates lack of consensus regarding target levels of serum calcium for treatment of a severe diltiazem intoxication. Goal‐directed tapering of calcium should prevent side effects of iatrogenic hypercalcaemia. The contribution of glucagon infusions is doubtful due to the instability of solubilized glucagon. This might explain why the effect of glucagon is variable in the literature.